A Syntactic and Morphological Analysis of “A Poem with Your Name” - Kadek Handini Putri; Putu Indri Cahyani (Universitas Bali Dwipa, 2024)
The purpose of this research is to examine the syntactic structures and morphological choices in “A Poem with Your Name,” specifically how these language components contribute to the poem’s emotional and artistic impact. The research aims to discover how language develops meaning and provokes emotions in poetry literature by focusing on syntax (sentence patterns) and morphology (word structures). The poem “A Poem with Your Name” provided the basis for this study’s data. The poem was evaluated qualitatively, with an emphasis on syntactic patterns like sentence complexity and inversions, as well as morphological aspects like derivations and compound words. The fundamental methodology consists of attentive reading and linguistic analysis, which are supported by frameworks from Chomsky’s syntactic theory and Jakobson’s poetic function. These results suggest that the way syntax and morphology interact is essential to the poem’s overall effect and offer new perspectives on how linguistic features influence literary meaning. Students and scholars in both linguistics and literature may find this study helpful as it highlights the need of applying linguistic frameworks to literary texts.